Improving the Vocabulary Mastery and Listening Skill at Junior High School Using Taylor Swift’s Songs - Kiki Anggreni; Erika Sinambela; Lastri Wahyuni Manurung (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The objective of this research was to find out whether the use of Taylor Swift’s songs can improve the Vocabulary Mastery and Listening Skill of seventh grade students at SMP Swasta Methodist-2 Medan ability using Taylor Swift’s songs and to know which skills improved more significantly. The method used here is Classroom Action Research (CAR). The data was obtained through quantitative method using tests and qualitative method using observation sheets and interview. The research subject were 29 students from class 7B of SMP Swasta Methodist-2 year 2022/23.  From the research findings, it was concluded that Taylor Swift’s songs improved students’ Vocabulary Mastery and Listening Skill. This is concluded from the results of the scores students achieved from Pre-Test to Post-Test. The Mean of the Vocabulary Pre-Test was 31.93 with 10.34% of the students passed the KKM. Then in the Cycle-1, The Mean was 72.31 with 62.07 of the students passing the KKM. Finally in Cycle-2, The Mean was 87.07 with 96.55% of the students passing the KKM. In Listening Skill, the Mean of the Pre-Test was 55.03 with 37.93% of the students passed the KKM. Then in the Cycle-1, The Mean was 91.34 with 96.55% of the students passing the KKM. Finally in Cycle-2, The Mean was 97.79 with 96.55% of the students passing the KKM. Based on the data, it can be concluded that the students’ Listening skill improved more significantly than Vocabulary Mastery. Based on the data, it can be concluded that the students’ Listening skill improved more significantly than Vocabulary Mastery.